Effectiveness of a measurement feedback system on outcome in rheumatoid arthritis: a controlled clinical trial. Issue 7 (1st July 2003) - Fransen, J; Stucki, G; Twisk, J; Chamot, A-M; Gerster, J-C; Langenegger, T; Seitz, M; Michel, B A; ,
Abstract : Background: With the help of a measurement feedback system, the treatment strategy for individual patients with rheumatoid arthritis (RA) can be adjusted to achieve optimal control of disease activity. Objective: To study whether a measurement feedback system is effective in reducing disease activity in patients with RA. Methods: Forty eight rheumatologists and 264 patients participated in a controlled clinical trial. A three month control period was followed by a 12 month period, where feedback on disease activity, disability, and damage was provided to the rheumatologist. The primary outcome measure was the rheumatoid arthritis disease activity index (RADAI). Results: The feedback system was used for 142/228 (62%) patients. Disease modifying antirheumatic drug changes occurred in 69/169 (41%) patients. In patients with high disease activity and feedback use (n=70), the RADAI decreased in the feedback period by –0.27 points per 30 days (p<0.05), as compared with the control period. Patients for whom the feedback system was used had a better outcome than non-users. Conclusion: Much more training on the use of a feedback system and outcome measures, as well as the inclusion of explicit treatment guidelines will be necessary to increase the clinical use of measurement feedback and, possibly, to reduce disease activity for a larger number of patients with RA.